2021
DOI: 10.3390/jcm10143147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic RAAS Use in Elderly COVID-19 Patients: A Retrospective Analysis

Abstract: Corona Virus Disease-19 (COVID-19) recently emerged as a global pandemic. Advanced age is the most important risk factor for increased virus susceptibility and worse outcomes. Many older adults are currently treated with renin–angiotensin–aldosterone system (RAAS) inhibitors and there is concern that these medications might increase the risk of mortality by COVID-19. This is a retrospective cohort of 346 patients older than 65 years with COVID-19, at the Department of Medicine of the Centro Hospitalar Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…In agreement with our results, the association found was independent from indicators of disability and disease severity (29). Oliveira et al (30) found a 73% lower risk of mortality for patients chronically taking RASi in a geriatric population with an average age slightly lower than ours (mean age: 80.9 ± 8.7 years). Moreover, a recently published Italian study found that antecedent use of RASi was associated with lower mortality in hypertensive COVID-19 patients aged 68 years and older (31).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, the association found was independent from indicators of disability and disease severity (29). Oliveira et al (30) found a 73% lower risk of mortality for patients chronically taking RASi in a geriatric population with an average age slightly lower than ours (mean age: 80.9 ± 8.7 years). Moreover, a recently published Italian study found that antecedent use of RASi was associated with lower mortality in hypertensive COVID-19 patients aged 68 years and older (31).…”
Section: Discussionsupporting
confidence: 92%
“…A French observational study, conducted in a geriatric department, also showed a lower mortality rate in oldest old patients (mean age: 86.3 ± 8.0 years) taking ACEIs/ARBs compared with patients not taking these drug classes [68]. These data on older subjects have been confirmed by other observational studies on hospitalized patients, providing additional evidence on the benefit of RAS inhibitor use in this peculiar population [69,70]. On the other side, ACEIs/ARBs withdrawal was found to be associated with greater risk for complications and mortality in hospitalized COVID-19 patients that were previously taking these drugs, as per indication [71], while several large systematic reviews and cohort studies showed how their assumption/continuation was not harmful, firmly advising against their discontinuation [72][73][74][75].…”
Section: Arterial Hypertensionsupporting
confidence: 54%
“…On the other side, statins, cornerstone drugs in dyslipidemia and cardiovascular disease, demonstrated significant beneficial effects in patients with COVID-19, reducing in-hospital mortality in several observational studies [89][90][91] and meta-analyses [92,93], although not all studies are in agreement [94]. These beneficial properties, already suggested in previous studies on hospitalized patients [69], might be mediated by their speculative pleiotropic effects, including anti-inflammatory, immunomodulatory, and antithrombotic properties, but the atherosclerotic plaques stabilization, thus avoiding acute cardiovascular ischemic events that often complicate severe COVID-19, is likely to play the key role [70,[95][96][97][98]. Moreover, several experimental models pointed out their possible inhibitory action on the "classic RAS", ameliorating Ang II-mediated cardiac hypertrophy and fibrosis [98,99].…”
Section: Dyslipidemiamentioning
confidence: 67%
“…Blue-squared box, effect estimate; Green diamond, the pooled effect estimate; Gray vertical line, no effect line; Red vertical line, the pooled effect estimate; N, number of individuals; SD, standard deviation; Mean Diff, mean difference. Remended from Carpenè et al (2021) (86) and (87)(88)(89)(90)(91)(92)(93)(94)(95)(96).…”
Section: Supplementary Figurementioning
confidence: 99%